Perceptions of meritocracy in Singapore : inconsistencies, contestations and biases - Teo, Terri-Anne (2021)
This article questions how meritocracy, as a state-sponsored narrative in Singapore, is variously negotiated and interpreted by Singaporean youth. Conveyed as a tenet central to Singapore’s national identity, meritocracy is often referred to as the “Singapore Dream” where socioeconomic mobility is made possible through hard work and ability regardless of ethnic difference. Critics of meritocracy in Singapore problematise how the narrative exists as a political instrument, conceals systemic discrimination and perpetuates ethnic inequality. Yet, how the population receives meritocracy remains unexplored within scholarship. While recognising its dominance within Singapore’s socio-political landscape, this article takes a bottom-up approach to understanding how meritocracy is perceived on the ground. Interviews conducted with Singaporean polytechnic students reveal differential experiences and articulations of meritocracy, demonstrating a gap between the endorsement of meritocracy as a positive value and conviction that it exists in practice. Furthermore, where ethnic discrimination is recognised among Singaporean youth, it is oftentimes normalised as a function of a multiracial society. This belief is problematic as it vindicates state and society and reduces the impetus to seek redress and change.